2019
DOI: 10.1021/acs.jpcc.8b11914
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Conducting Properties and Fuel Cell Performance Developed by Band Structures

Abstract: The layer-structure transition-metal oxides have good triple H + / O 2− /e − charge transport which can promote redox reactions and enhance fuel cell performance. This work has developed ionic transport property based on the layer-structure LiCoO 2 (LCO) by tuning the energy band structure with Mg doping also applied for the electrolyte in high-performance lowtemperature solid oxide fuel cells (LT-SOFCs). Mg-doped LiCoO 2 exhibited a hexagonal-layered structure with the R3m space group. By doping LiCoO 2 , its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…The energy gap ( E g ) is the energy needed to move an electron from the valence to the conduction band. It is observed that with the increasing doping of Co (from 10% to 20% in SrCoSnO 3−δ ) the absorption band edge is red-shifted, indicating that these highly doped materials change their bandgap to a small bandgap, as depicted in Figure (a) . The calculated bandgaps are 2.11 and 2.0 eV, respectively, for SrCo 0.1 SnO 3−δ and SrCo 0.2 SnO 3−δ , as depicted in Figure (b).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The energy gap ( E g ) is the energy needed to move an electron from the valence to the conduction band. It is observed that with the increasing doping of Co (from 10% to 20% in SrCoSnO 3−δ ) the absorption band edge is red-shifted, indicating that these highly doped materials change their bandgap to a small bandgap, as depicted in Figure (a) . The calculated bandgaps are 2.11 and 2.0 eV, respectively, for SrCo 0.1 SnO 3−δ and SrCo 0.2 SnO 3−δ , as depicted in Figure (b).…”
Section: Resultsmentioning
confidence: 85%
“…The obtained values of VB, CB, and bandgap were used to construct the energy band diagram, as exhibited in Figure (e). The performance and electronic (hole) conduction might be enhanced due to the narrow bandgap or band bending …”
Section: Resultsmentioning
confidence: 99%
“…La-doped PO 4 , NbO 4 , and CeO 2 have reasonable proton conduction at intermediate temperatures. The BCFZY (BaCo 0.4 Fe 0.4 Zr 0.1 Y 0.1 O 3−δ ) triple conducting cathode has also reported that doping of Co and Fe on the B-site of perovskite BZY (H + /O 2– ) exhibited a high performance of 445 mW/cm 2 and high conduction (H + /O 2– /e – ) at 550 °C . It has also been reported that via high doping of Co/Fe at the B-site, BZY still maintained its ionic conductivity and catalytic performance . Traditional proton-conducting CFCs use proton-conducting oxide electrolytes such as BZY and Y-doped BaCeO 3 (BCY), which have enabled operating fuel cells at low temperature. , However, new developments on using semiconductors, e.g., SNO (SmNiO 3 ), STO (SrTiO 3 ), LST (La-SrTiO 3 ), TiO 2 , and ZnO, to replace commonly used BZY or BCY, show advantages in enhancing both the ionic conductivity and device performance. Moreover, much progress has been made in oxide materials, especially to maintain the protons, dual ions (H + /O 2– ), and triple-charge conduction, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…13 It has also been reported that via high doping of Co/Fe at the B-site, BZY still maintained its ionic conductivity and catalytic performance. 14 Traditional protonconducting CFCs use proton-conducting oxide electrolytes such as BZY and Y-doped BaCeO 3 (BCY), which have enabled operating fuel cells at low temperature. 13,15 However, new developments on using semiconductors, e.g., SNO (SmNiO 3 ), STO (SrTiO 3 ), LST (La-SrTiO 3 ), TiO 2 , and ZnO, to replace commonly used BZY or BCY, show advantages in enhancing both the ionic conductivity and device performance.…”
Section: Introductionmentioning
confidence: 99%
“…The heterojunction space charge region and ion concentration potential have a synergistic effect on the charge transport in SBFCs. Hence, there exist two driving forces for ionic transport in SBFCs, one is the chemical concentration gradient and the other is the BIEF force (Ganesh et al, 2019;Mushtaq et al, 2019). In addition, SBFCs are built on the semiconductors or SIMs possessing mixed ionic and electronic conduction, which can build up the three-phase boundary (TPB) to promote the HOR and ORR processes (Meng et al, 2018;Chen et al, 2019).…”
Section: Comparison Between Sbfcs Based On Different Heterojunctionsmentioning
confidence: 99%